Mr Stink - Walliams, David; Blake, Quentin (HarperCollins Children's Books, is a division of HarperCollinsPublishers Ltd London, 2015)
Chloe's a bit unpopular, a little lonely and completely overshadowed by her disgustingly talented sister. But then Chloe meets Mr Stink, the local tramp. Yes, he smells a bit. But he's the only person who's ever been nice to her and that includes her awful snob of a mother. So when Chloe's mother stands for election, promising to rid the town of tramps, it looks like Chloe might be about to lose her only friend